READING HABITS AND PREFERENCES: THE CONTEXT OF READER’S EXPERIENCE - Kulikauskienė, Kristina; Naujokienė, Laima (PROFESSIONAL STUDIES: Theory And Practice, 2023)
In this article the reading habits and preferences form the reader’s perspective, highlighting the factors that have impact on reading experience are analyzed. The theoretical analysis of the scientific literature and empirical study revealed that reading habit can be quantified in terms of the materials read, frequency of reading, and amount of time spent reading, or in other words, by established reading preferences. Reading habits and preferences are influenced by a variety of factors, which are internal (age, gender, free time etc.) and external (technology advancement, crisis situations, etc.), reading habits and preferences may alter over time.